2011
DOI: 10.1099/vir.0.028894-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of immunostimulatory components of orf virus (parapoxvirus ovis)

Abstract: Inactivated orf virus (ORFV, parapoxvirus ovis) induces antiviral activity in animal models of acute and chronic viral infections and exerts strong effects on human immune cells. ORFV activates antigen presenting cells (APC) via CD14 and, probably, Toll-like receptor signalling, and triggers the release of IFN-c that has been identified as the key mediator of the antiviral activity. After delineating virus proteins as being the most likely active constituent, we aimed to characterize the ORFV proteins responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
1
32
1
Order By: Relevance
“…Prevention and control of the disease cannot only improve the economic efficiency in sheep industry, but also has important public health implications. Although whole genome sequences for four strains of ORFV (OV-SA00, OV-IA82, NZ2 and D1701) have been deposited in the GenBank, functions of many genes are still poorly understood (Delhon et al, 2004;Friebe et al, 2011). Comparison of the whole genome sequence of sheep ORFV isolate (OVIA82) and goat isolate (OV-SA00) with bovine papular stomatitis virus isolate indicated that ORFV contained 132-134 ORFs (Delhon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention and control of the disease cannot only improve the economic efficiency in sheep industry, but also has important public health implications. Although whole genome sequences for four strains of ORFV (OV-SA00, OV-IA82, NZ2 and D1701) have been deposited in the GenBank, functions of many genes are still poorly understood (Delhon et al, 2004;Friebe et al, 2011). Comparison of the whole genome sequence of sheep ORFV isolate (OVIA82) and goat isolate (OV-SA00) with bovine papular stomatitis virus isolate indicated that ORFV contained 132-134 ORFs (Delhon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the whole genome sequence of sheep ORFV isolate (OVIA82) and goat isolate (OV-SA00) with bovine papular stomatitis virus isolate indicated that ORFV contained 132-134 ORFs (Delhon et al, 2004). Furthermore, virulence and immune regulation-related genes were concentrated at the terminal inverted repeats (ITRs) region of the ORFV genome (Haig and Fleming, 1999;McInnes et al, 2001;Friebe et al, 2011). At present, only some ORFV virulence factors have been confirmed, which include viral interferon inhibitory protein (OVIFN, ORF020) , chemokine binding protein (CBP, ORF112) (Seet et al, 2003), GM-CSF/IL-2 inhibitory factor (GIF, ORF117) (Deane et al, 2000), viral interleukin 10 (VIL-10, ORF127) (Fleming et al, 1997;Chan et al, 2006) and vascular endothelial growth factor (VEGF, ORF132) (Lyttle et al, 1994;Savory et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Immune modulation by iPPVO has been investigated in several systems and was primarily associated with stimulation of a broad range of cytokines, including proinflammatory and Th1- and Th2-related cytokines (29). This complex cytokine response is also associated with the activation of several cell populations, including monocytes and Th1-like cells, human neutrophils, canine monocytes, and murine bone marrow-derived dendritic cells (BMDCs), among others (13,15-18,29,30). Most of these studies focused on in vitro stimulation of specific cell populations by preparations of iPPVO.…”
Section: Discussionmentioning
confidence: 99%
“…The short-term vector-specific immunity and the lack of serum antibodies efficiently neutralizing ORFV (38,40) enable repeated immunizations with the same or with different ORFV recombinants. Unique immune-modulating properties of ORFV strongly stimulate the innate immunity (40)(41)(42)(43) and rapidly generate foreign antigen-specific immune responses (44)(45)(46)(47). The apathogenic, Vero cell culture-adapted ORFV strain D1701-V is used to generate recombinants by substituting the viral vegf-e gene with a foreign gene, which thereby removes an ORFV virulence gene and leads to further attenuation (38,44,48).…”
mentioning
confidence: 99%